(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Biblionline Vol. 7, n.2 (2011) Link de acesso ao número http://periodicos.ufpb.br/ojs2/index.php/biblio/issue/view/1002/showToc